PENERAPAN TEORI ETIKA UTILITARIANISME DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH-SEKOLAH INDONESIA - Franciscus Ari Setyawan; Istiana Hermawati (ADISAM PUBLISHER, 2024)
The implementation of the Merdeka Curriculum in Indonesian schools can be analyzed through the lens of the ethical theory of utilitarianism, which emphasizes achieving the greatest happiness for the greatest number of people. The Merdeka Curriculum is designed to provide flexibility to schools and teachers in compiling and implementing the curriculum, according to student needs and potential. This approach is expected to increase student engagement and learning motivation, empower teachers to develop innovative teaching methods, and create more relevant and contextual learning. In addition, the Merdeka Curriculum also aims to ensure equal access to education and fair opportunities for all students, including those who have special needs or come from different socio-economic backgrounds. Although the implementation of this policy faces challenges, such as disparities in educational quality between schools and administrative burdens for teachers, the potential to improve educational quality and collective welfare remains significant. Thus, the application of the ethical theory of utilitarianism in the Independent Curriculum is expected to bring maximum benefits to all stakeholders in the Indonesian education system